Spatial distribution and influencing factors of CDC health resources in China: a study based on panel data from 2016–2021 - Yu, Yingying; Lu, Jiachen; Dou, Xiaofeng; Yi, Yaohui; Zhou, Ling (Frontiers in Public Health, 2024)
Background: Measuring the development of Chinese centers for disease control and prevention only by analyzing human resources for health seems incomplete. Moreover, previous studies have focused more on the quantitative changes in healthcare resources and ignored its determinants. Therefore, this study aimed to analyze the allocation of healthcare resources in Chinese centers for disease control and prevention from the perspective of population and spatial distribution, and to further explore the characteristics and influencing factors of the spatial distribution of healthcare resources.Method: Disease control personnel density, disease control and prevention centers density, and health expenditures density were used to represent human, physical, and financial resources for health, respectively. First, health resources were analyzed descriptively. Then, spatial autocorrelation was used to analyze the spatial distribution characteristics of healthcare resources. Finally, we used spatial econometric modeling to explore the influencing factors of healthcare resources.The global Moran index for disease control and prevention centers density decreased from 1.3164 to 0.2662 (P < 0.01), while the global Moran index for disease control personnel density increased from 0.4782 to 0.5067 (P < 0.01), while the global Moran index for health expenditures density was statistically significant only in 2016 (P < 0.1). All three types of healthcare resources showed spatial aggregation.Population density and urbanization have a negative impact on the disease control and prevention centers density. There are direct and indirect effects of disease control personnel density and health expenditures density. Population density and urbanization had significant negative effects on local disease control personnel density. Urbanization has an indirect effect on health expenditures density.There were obvious differences in the spatial distribution of healthcare resources in Chinese centers for disease control and prevention. Social, economic and